From the editors - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
From the Editors SPECIAL ISSUE: LANGUAGE VALUE IN MINORITY LITERATURES In the wake of Nigerian independence and in contrast to African writers who took an essentialist view that equates language with cultural identity (Ngugi wa Thiong'o, for example), Chinua Achebe declared that "[a] language spoken by Africans on African soil, a language in which Africans write, justifies itself" (1975: 67). According to his vision, the colonizers' languages, English and French, even if they were not African languages, because of their grasp on African history, were part and parcel of African experience. [...]